Thermal exposure of implant osteotomies and its impact on osseointegration—A preclinical in vivo study. Issue 6 (21st March 2021) - Heuzeroth, Raphael; Pippenger, Benjamin E.; Sandgren, Rebecca; Bellón, Benjamin; Kühl, Sebastian
Abstract: Objectives: Thermal and mechanical stresses during osteotomy preparation can impair implant osseointegration. This study investigated implant osseointegration following the measurement of temperature exposure during osteotomy drilling, varying drill design, sequence, and drill wear. Materials and methods: 36 tapered implants were placed in a mandibular minipig model after guided drilling of implant osteotomies using 4 different groups: (1) control drills with a conservative, sequential drilling sequence, (2) control drills using a shortened drill sequence (PF), (3) novel test drill displaying an optimized drill design and surface treatment, PF, and (4) aged test drill, PF. Intraosseous temperatures during drilling were measured using a temperature probe. BIC, fBIC, and tissue reactions were histomorphometrically derived after 2 and 8 weeks of healing. Results: Compared to control drills (1) or (2), test drills (3) resulted in significantly lower maximum temperatures ((35.4 (CI 30.2–40.5)°C vs. (46.5 (CI 41.0–52.0)°C, p  = .0021)) and shorter drill times ((4.5 (CI 1.6–7.3)sec vs. 10.3 (7.3–13.4)sec). Lower osteotomy temperature values and shorter drill times corroborated with significantly higher BIC after 2 and 8 weeks healing for the test (3) compared to control groups (2) (2 weeks: (44.9 (CI 34.1–55. 7)% vs. (31.3 (CI 20.5–42.2)%, p  = <.0001 and 8 weeks: (73.7 ( CI 64.2–83.2)% vs. (66.2 (CI 57.0–75.4)%, p  = <.0455). Conclusion: The improved osseointegration of implants placed after osteotomy preparation with novel test drills using a shortened drill sequence compared to standard drills and conventional drill protocols might be attributed to more favorable thermal profiles and less mechanical stress exerted on the bone surrounding the implant osteotomy.